2006
DOI: 10.1186/1747-597x-1-7
|View full text |Cite
|
Sign up to set email alerts
|

I love you ... and heroin: care and collusion among drug-using couples

Abstract: Background: Romantic partnerships between drug-using couples, when they are recognized at all, tend to be viewed as dysfunctional, unstable, utilitarian, and often violent. This study presents a more nuanced portrayal by describing the interpersonal dynamics of 10 heroin and cocaine-using couples from Hartford, Connecticut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 37 publications
2
84
1
Order By: Relevance
“…Nonetheless, many still have supportive family, partners, and friends, including individuals who both do and do not themselves use drugs (Neale, Pickering, & Nettleton, 2012;Neale, 2001;Simmons & Singer, 2006). These more supportive relationships have been shown to discourage drug use and enable better management of addictions (Alverson, Alverson, & Drake, 2000;Laudet, Magura, Vogel, & Knight, 2000).…”
Section: Introductionmentioning
confidence: 93%
“…Nonetheless, many still have supportive family, partners, and friends, including individuals who both do and do not themselves use drugs (Neale, Pickering, & Nettleton, 2012;Neale, 2001;Simmons & Singer, 2006). These more supportive relationships have been shown to discourage drug use and enable better management of addictions (Alverson, Alverson, & Drake, 2000;Laudet, Magura, Vogel, & Knight, 2000).…”
Section: Introductionmentioning
confidence: 93%
“…Like Stuart, Giuseppe sees his hepatitis C as having limited his chances of experiencing 'normal' love and intimacy: The accounts provided by both Stuart and Giuseppe challenge common assumptions about the lack of desire on the part of injecting drug users for normative experiences of love and intimacy. Like the participants in Simmons and Singer's (2006) study, they share the same hopes as non-injecting drug users for enduring relationships, love, stability and parenthood.…”
Section: Resultsmentioning
confidence: 88%
“…In these representations, 'normal' intimacy is beyond the capacities of injecting drug users, who are presented as capable only of intimate attachment to drugs (Keane, 2004). However, some research suggests that contemporary notions of romantic love and intimacy do indeed shape the experiences of injecting drug users (Bourgois, Prince, & Moss, 2004;Jackson, Parker, Dykeman, Gahagan, & Karabanow, 2009;Rhodes & Cusick, 2000;Simmons & Singer, 2006). For example, modern notions of intimacy and romantic love, and their promise to 'secure self-identities in a world characterized by uncertainty' (Rhodes & Cusick, 2000, p. 4), can shape the ways in which people who inject drugs assess and respond to risk.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have suggested that sexual relationships shape the ways PWID think about, discuss and act on bloodborne virus prevention. Needle sharing between sexual partners can result in or act as a sign of emotional bonding, commitment, fidelity, mutual trust and shared intimacy (Davies et al, 1996;Habib, 2003;Lakon, Ennett, & Norton, 2006;MacRae, 2000;Rhodes & Quirk, 1998;Simmons & Singer, 2006). Refusal to share can introduce the suggestion of distrust and a denial of intimacy (Barnard, 1993;Dear, 1995;Unger et al, 2006).…”
Section: The Social Relations Of Hepatitis Cmentioning
confidence: 95%